Pertumbuhan lobster air tawar Cherax quadricarinatus (Von Martens, 1868) yang diberi pakan Keong Tutut Jawa Filopaludina javanica (Von Dem Busch, 1844) - Erwin Wiradita Mamonto; Winda Mercedes Mingkid; Revol D. Monijung; Henneke Pangkey; Nego Elvis Bataragoa (Universitas Sam Ratulangi, 2023)
The research was carried out to investigate the best amount of large freshwater snail (Filopaludina javanica) meat as feed for the growth and survivals (SR) of freshwater lobster C. quadricarinatus. The size of freshwater lobster used in this study was 1.70 – 23.90 gr. Lobsters were kept in aquariums measuring 30 x 30 x 40 cm for 30 days. The experimental design used was a completely randomized design (CRD) with three treatments and three replications that is A (4%), B (7%) and C (10%) of feed. Data analysis was used linier regression. The results showed the (R2) marks close to 1 means that the time of experiment effects the growth of lobster in all treatments, 4% feed (R2 =0,8919), 7% (R2=0,9942) and 10%(R2=0,9484, where the highest coefficient regression was treatment B (0,5818) followed by treatment A (0,4625) and C (0,42), respectively. The highest survival rate was found in treatment B (91.7%), treatment A (75%) and C (66.7%), respectively. Results of analysis showed that the size and the length of time of experiment effects the time of growth and survival.